Perceptions on F/OSS adoption - Oba, Beyza (My University, 2007)
This paper aims to reveal results of a survey run by the tOSSad 1 project. The majority of survey variables devised to capture perception of public administrators around Europe regarding the importance they attach to the factors such as F/OSS product quality, availability of support, expertise and documentation, TCO, vendor lock-in, political influence, administrative attitudes, productivity, and training costs, all of which intermingle with financial, technical, legal, and personal issues. The analysis consist of depiction of respondents' administration profile in terms of their F/OSS usage and adoption, descriptive summary and analyses of factors mentioned above, and statistical inferential analyses of survey items. Some valid statistical tests are conducted to understand, to discuss and to see the extend and significance of any F/OSS adoption generalizations for Europe based on the findings of this particular survey. © 2007 International Federation for Information Processing.
Keywords: Open systems; Software engineering; Lock-in; Political influences; Public administrators; Training costs; Surveys